Estimation of outflow discharge from an ungauged river: case study of Awara in Ondo State Southwestern, Nigeria (2017)
Flooding has become the annual experience of Nigerian cities especially in the southwestern states of country, precisely Ondo state. This study uses Muskingum Cunge method river routing techniques to compute outflow discharge and to determine hydrographs of inflow and outflow pattern of Awara river Ikare Akoko, North east LGA in Ondo State, Southwestern of Nigeria. The Muskingum Cunge method of flood routine reflects the interrelationship existing between the inflow and outflow of river. The average monthly inflow discharge for twenty years was worked on using Muskingum Cunge method of flood routine. Observation from the hydrograph shows th'at inflow peak occurs in the month of April, while the outflow in the same month is very low. This implies that the month of April is a critical month that needs a special attention and there is a need for channelization of this river before the month of April every year, in order to prevent occurrence of flooding whenever there is heavy rainfall.